2021
DOI: 10.3390/jof7070550
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microbiota and Mycobiota in Fungal Ball Rhinosinusitis: Specific Interaction between Aspergillus fumigatus and Haemophilus influenza?

Abstract: Fungal ball (FB) rhinosinusitis (RS) is the main type of non-invasive fungal RS. Despite positive direct examination (DE) of biopsies, culture remains negative in more than 60% of cases. The aim of the study was to evaluate the performance/efficacy of targeted metagenomics (TM) to analyze microbiota and mycobiota in FB and find microbial associations. Forty-five sinus biopsies from patients who underwent surgery for chronic RS were included. After DE and culture, DNA was extracted, then fungal ITS1–ITS2 and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
4
2
Order By: Relevance
“…Delliere et al identified Aspergillus spp. in 89.5% of fungal balls with targeted metagenomics 3 . However, in our study, 60.71% of the reads from each fungal sample could not be assigned to an OTU and were, thus, annotated as unclassified.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Delliere et al identified Aspergillus spp. in 89.5% of fungal balls with targeted metagenomics 3 . However, in our study, 60.71% of the reads from each fungal sample could not be assigned to an OTU and were, thus, annotated as unclassified.…”
Section: Discussioncontrasting
confidence: 61%
“…in 89.5% of fungal balls with targeted metagenomics. 3 However, in our study, 60.71% of the reads from each fungal sample could not be assigned to an OTU and were, thus, annotated as unclassified. The ability to assign a significant number of reads at both the phylum and genus levels reveals the presence of several formerly unknown fungal taxonomic groups in fungal sinusitis and recapitulates the limitations of the existing fungal sequence databases.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…(2017) revealed that levels of specific gatekeeping genera, such as Corynebacterium , Peptoniphilus , and Propionobacterium , have been reduced in the microbiota of CRS patients, which might predispose the host to pathogen-driven inflammation. So far, much effort has been done to define the relationship between the type and amount of the microorganism and the severity of CRS using similar methods in microbiota analysis ( Cho et al., 2021 ; Delliere et al., 2021 ; Stryjewska-Makuch et al., 2021 ). Collectively, these studies suggest that bacterial microbiota might play a pathogenic role in CRS, with significant implications for disease management and treatment.…”
Section: Introductionmentioning
confidence: 99%